2020
DOI: 10.2147/cmar.s237867
|View full text |Cite
|
Sign up to set email alerts
|

<p>MAGE-A11 Expression Predicts Patient Prognosis in Head and Neck Squamous Cell Carcinoma</p>

Abstract: Background: Head and neck squamous cell carcinomas (HNSCCs) are the sixth most common cancer worldwide. Growing evidence showed that Melanoma-associated antigen-A11 (MAGE-A11) was abnormally expressed in various malignancies, but MAGE-A11 expression and its biological roles in HNSCC had not been reported in detail. The aim of the study was to investigate the association between MAGE-A11 signatures and clinicopathological features of HNSCC patients and uncover its potential mechanisms in HNSCC patients. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…4D, Supplementary Notes). This locus, which contains the gene MAGEA11 implicated in cancer progression (James et al 2013;Su et al 2019;Jia et al 2020), was confidently identified as toggling using our tiSNP-and haplotype-based approaches (Table 1) and, additionally, was subject to inversion during primate genome evolution (Fig. S32).…”
Section: Imprecise Breakpoint Reuse In Further Support Of Inversion Recurrencementioning
confidence: 98%
“…4D, Supplementary Notes). This locus, which contains the gene MAGEA11 implicated in cancer progression (James et al 2013;Su et al 2019;Jia et al 2020), was confidently identified as toggling using our tiSNP-and haplotype-based approaches (Table 1) and, additionally, was subject to inversion during primate genome evolution (Fig. S32).…”
Section: Imprecise Breakpoint Reuse In Further Support Of Inversion Recurrencementioning
confidence: 98%
“…MAGEB6 presented significant association with poor disease outcome, whilst conversely, MAGEA3 and MAGEA6 were reported as a biomarker for longer disease-free survival (DFS) [ 129 ]. MAGEA11 mRNA expression was significantly associated with advanced clinical stage and metastasis in lymph nodes [ 134 ]. IgG antibody responses against MAGE antigens can be detected in HNSCC patients’ serum [ 130 ].…”
Section: Tumour-associated Antigens (Taas)mentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) has been introduced as the sixth most common malignancy globally. HNSCC originates from various subsites of the upper aerodigestive tract, such as the oral cavity, larynx, pharynx, paranasal sinuses and nasal cavity [1][2][3][4]. Despite current efforts for the risk stratification and treatment of patients with HNSCC, the overall survival (OS) rate of these patients is unsatisfactory and has not significantly improved over the past decade, which may be because of late-stage diagnosis.…”
mentioning
confidence: 99%